PENGEMBANGAN BUKU AJAR INOVATIF IPA TERPADU BERBASIS INKUIRI TERBIMBING SESUAI KURIKULUM 2013 DI SMP SE-KABUPATEN TAPANULI TENGAH - Bronika Septiani Sianturi; Jhonas Dongoran (Jurnal Darma Agung, 2019)
This research is a research and development which is aimed to produce a certain product or develop an existing product including test its effectiveness. The research and development procedures are included in stages such as: Potential and problems; Data collection; Product design; Design validation; Design revisions; Product I trial; Product I revision; Trial usage; Product Revision II; Mass product. The data analysis resulted as follows (1) in the teaching materials that have been developed on the subject matter of additives and addictive substances based on BSNP, (a) the aspects of content worthiness is 3.65 of mean, (b) the aspects of language worthiness is 3.70 of mean, (c) the aspects of the feasibility of serving with is 3.60 of mean, those score are valid and don’t need any revision and it is very decent. (2) It is the students understanding who use the material that has been developed, it obtained an average of 80.21. However the understanding of students who did not use the teaching materials developed just obtained an average of 65.00. This result shows that the understanding of students using the developed teaching materials is higher than without using developed teaching materials.